A Pattern of Economic Anaseism in Scientific and Technological Progress - Grishin, Mikhail (SHS web of conferences, 2021)
The article reveals and theoretically substantiates the anaseism (wave-like) nature of scientific and technological progress. The author of the article, in the course of his research activities, has developed a model of waves (anaseism) of scientific and technological progress, which reveals a natural sequence of the life cycle of any technology, start-up and other, both tangible and intangible objects of scientific and technological progress.